2017
DOI: 10.1111/pedi.12571
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is higher in prepubertal girls but switches to become higher in boys at age 16: A Cohort Study (EarlyBird 57)

Abstract: The higher IR of prepubertal and early pubertal girls diminishes during late puberty, and boys begin to exhibit greater metabolic risk. Despite being leaner and more active, boys at 16 years have higher IR than girls, suggesting future higher risk for diabetes, thus we reject our hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
5
25
0
Order By: Relevance
“…1) [9,[62][63][64][65][66]. This pattern was documented by insulin clamp studies among Caucasian and African-American youths, and persisted with adjustment for measures of adiposity, BMI and objective physical activity levels [63,64,66]. In one of the first mechanistic studies in Latino adolescents, both girls and boys increased insulin secretion to compensate for greater insulin resistance in early puberty [67].…”
Section: Mechanism Of Type 2 Diabetes Onset In Youthmentioning
confidence: 86%
See 1 more Smart Citation
“…1) [9,[62][63][64][65][66]. This pattern was documented by insulin clamp studies among Caucasian and African-American youths, and persisted with adjustment for measures of adiposity, BMI and objective physical activity levels [63,64,66]. In one of the first mechanistic studies in Latino adolescents, both girls and boys increased insulin secretion to compensate for greater insulin resistance in early puberty [67].…”
Section: Mechanism Of Type 2 Diabetes Onset In Youthmentioning
confidence: 86%
“…Despite accounting for these individual-level predictors of insulin resistance, sex differences in insulin resistance across the childhood life-phase exist: females have higher rates of insulin resistance than males from early childhood through to mid-puberty, whilst, during late puberty and adulthood, males exhibit greater insulin resistance than females ( Fig. 1) [9,[62][63][64][65][66]. This pattern was documented by insulin clamp studies among Caucasian and African-American youths, and persisted with adjustment for measures of adiposity, BMI and objective physical activity levels [63,64,66].…”
Section: Mechanism Of Type 2 Diabetes Onset In Youthmentioning
confidence: 99%
“…Insulin resistance rises progressively from age 7 years, a few years before the first pubertal signs, and increases further at puberty ( 32 ). At puberty there is also a switch: prepubertal girls have higher insulin resistance but boys exhibit a higher metabolic risk by the end of puberty ( 33 ). These findings may partly explain the complexity of our results: S-INS and HOMA-IR increased in prepubertal girls and boys, despite of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, Framingham Heart Study showed that asparagine was inversely associated with fasting insulin while aspartate was inversely associated with fasting glucose (16); overweight/obese pregnant women had a higher total amount of asparagine and aspartate (17). Interestingly, these traits and pathways were previously found to be associated with crucial mechanisms which contributed to sex difference in different age groups, for example, higher insulin resistance in males than females before older life (5) and sudden de ciency of estrogens due to menopause at ~ 50 years of age in females (18)(19)(20). Hence, it was possible that asparagine and aspartate homeostasis might help interpret these sex-speci c mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…There is a small but signi cant sex differences in the prevalence of type 2 diabetes (T2D) globally (1)(2)(3). Crosssectional and prospective investigations all showed that males are more likely to have insulin resistance and to have higher prevalence of diabetes in late adolescence up to midlife than females (4,5). Females experienced a sharply increased risk of diabetes after the menopause, resulting in nearly equal prevalence of T2D as males in older life (1,2,6).…”
Section: Introductionmentioning
confidence: 99%